2018
DOI: 10.1177/1352458518765654
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of salivary human herpesviruses in pediatric multiple sclerosis cases and controls

Abstract: None of these mutations were evident in EBV-positive samples from pediatric MS patients, whereas they were present in pediatric controls, in addition to MS and control adults, suggesting differential host-immune control of EBV in this pediatric MS cohort.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 35 publications
2
7
0
3
Order By: Relevance
“…We demonstrated that some copies of HHV-6B in saliva acquire a telomere, indicative of integration in somatic cells in vivo and as previously detected in vitro (Arbuckle et al, 2010). The viral load in the saliva samples was low, as seen in some other studies (Leibovitch et al, 2014;Leibovitch et al, 2019;Turriziani et al, 2014), and the number of HHV-6B genomes with a telomere was small (Figure 4, Supplementary Table 3), which is consistent with the majority of HHV-6B genomes present as viral particles in saliva (Jarrett et al, 1990). The approach we used to detect telomeric integration in saliva could, in principle, be used to detect HHV-6B integration events in sperm from healthy non-iciHHV-6B men (Neofytou et al, 2009) (Godet et al, 2015Kaspersen et al, 2012).…”
Section: Discussionsupporting
confidence: 87%
“…We demonstrated that some copies of HHV-6B in saliva acquire a telomere, indicative of integration in somatic cells in vivo and as previously detected in vitro (Arbuckle et al, 2010). The viral load in the saliva samples was low, as seen in some other studies (Leibovitch et al, 2014;Leibovitch et al, 2019;Turriziani et al, 2014), and the number of HHV-6B genomes with a telomere was small (Figure 4, Supplementary Table 3), which is consistent with the majority of HHV-6B genomes present as viral particles in saliva (Jarrett et al, 1990). The approach we used to detect telomeric integration in saliva could, in principle, be used to detect HHV-6B integration events in sperm from healthy non-iciHHV-6B men (Neofytou et al, 2009) (Godet et al, 2015Kaspersen et al, 2012).…”
Section: Discussionsupporting
confidence: 87%
“…23 Observation of viral messenger RNA (mRNA) and protein expression in oligodendrocytes further contributed to the hypothesis of HHV-6 as a driver of MS. 23 Subsequent studies have shown extreme variability in IgG-and IgM-specific responses to viruses isolated from CSF, as well as to viral antigens or DNA from MS lesions. [24][25][26][27] Like other herpes viruses, HHV-6 is ubiquitous in the general population and typically acquired decades before disease presentation, complicating interpretation on how they might contribute to disease. Nor is there, to date, any effective, specific anti-HHV-6 intervention to employ in clinical trials of patients with MS or other HHV-6-associated CNS disorders, to prove a potential link to pathogenesis.…”
Section: Viral Triggersmentioning
confidence: 99%
“…Interestingly, in a small nonhuman primate model with prior HHV-6 infection (HHV-6 inoculated marmosets), subsequent induction of an MS-like experimental neuroinflammatory disease resulted in significantly poorer outcome compared to controls. 27…”
Section: Infectious Triggers In Msmentioning
confidence: 99%
See 2 more Smart Citations